2009
DOI: 10.1590/s0100-54052009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Danos causados pelo Zucchini lethal chlorosis virus (ZLCV) sobre a produção de frutos comerciais de abobrinha de moita 'Caserta'

Abstract: O ZLCV é um tospovírus encontrado com freqüência causando severos danos em cucurbitáceas. Nesse trabalho avaliaram-se os danos causados pelo ZLCV em abobrinha de moita 'Caserta', em campo na ESALQ/USP, Piracicaba-SP, onde esse vírus é freqüente. Plantas obtidas pela semeadura direta foram monitoradas periodicamente quanto à infecção pelo ZLCV por meio dos sintomas e por PTA-ELISA. Monitorou-se ainda a contaminação com Papaya ringspot virus - type W e Zucchini yellow mosaic virus, desconsiderando a produção des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…The results of this study, together with those reported by Yuki et al (2000), Giampan et al (2009) and Spadotti et al (2013), indicate that several species in the family Cucurbitaceae are naturally susceptible to infection with ZLCV. Thus, the current main strategy to eliminate or reduce the damage caused by ZLCV in cucurbit crops should focus mainly on the outside sources of inoculum.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study, together with those reported by Yuki et al (2000), Giampan et al (2009) and Spadotti et al (2013), indicate that several species in the family Cucurbitaceae are naturally susceptible to infection with ZLCV. Thus, the current main strategy to eliminate or reduce the damage caused by ZLCV in cucurbit crops should focus mainly on the outside sources of inoculum.…”
supporting
confidence: 82%
“…Infected plants die within a short time, especially when infection occurs before flowering (Bezerra et al 1999;Rezende et al 1997). Giampan et al (2009) found that zucchini squash plants exhibiting symptoms of ZLCV infection in the field 23 days after emergence (dae) did not produce marketable fruits, which could only be harvested from plants showing symptoms from 42 dae, but with a 78.5 % reduction in production.…”
mentioning
confidence: 99%
“…Caserta plants inoculated with PRSV-W and ZYMV, alone and together, at 5, 15 and 20 days after plant emergence in the field. For the disease caused by ZLCV, Giampan et al (2009) reported that zucchini squash plants that showed symptoms of virus infection up to 23 days after emergence in the field did not yield any fruit. Marketable fruits were first harvested only from plants that showed symptoms 42 days after emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Marketable fruits were only harvested from plants that showed symptoms at least 42 DAE, although these plants also demonstrated a 78.5% yield loss (Giampan et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants exhibiting symptoms 23 days after emergence (DAE) did not produce marketable fruit. Marketable fruits were only harvested from plants that showed symptoms at least 42 DAE, although these plants also demonstrated a 78.5% yield loss (Giampan et al 2009). ZLCV, genus Tospovirus, family Bunyaviridae (Pozzer et al 1996;Bezerra et al 1999), is transmitted by the thrips Frankliniella zucchini in a circulative propagative manner (Nakahara and Monteiro 1999).…”
Section: Introductionmentioning
confidence: 99%